Hyperactivation of mammalian target of rapamycin complex 1 by HIV‐1 is necessary for virion production and latent viral reactivation. Issue 1 (4th October 2016) - Kumar, Binod; Arora, Sakshi; Ahmed, Shaista; Banerjea, Akhil C.
Abstract : Generation of new HIV‐1 virions requires the constant supply of proteins, nucleotides, and energy; however, it is not known which cellular pathways are perturbed and what molecular mechanisms are employed. We hypothesized that HIV‐1 may regulate pathways that control synthesis of biomolecules in the cell. In this study, we provide evidence that HIV‐1 hyperactivates mammalian target of rapamycin complex 1 (mTORC1), the central regulator of biosynthesis. Mechanistically, we identify the viral regulatory gene tat (transactivator) as being responsible for increasingm TORC1 activity in aPI3K‐dependentmanner. Furthermore, we show that hyperactivation of mTORC1 leads to activation of the enzyme, carbamoyl‐phosphate synthetase 2, aspartate transcarbamylase, dihydroorotase, and repression of initiation factor 4E‐binding protein 1 activity. These are regulators of nucleotide biogenesis and protein translation, respectively. Moreover, we are able to replicate these results inHIV‐1 latent cell line models. Finally, we show that inhibition of mTORC1or PI3K inhibits viral replication and viral reactivation as a result of a decrease in biosynthesis. Overall, our study identifies a new avenue in HIV‐1 biology that can lead to development of novel therapeutic targets.—Kumar, B., Arora, S., Ahmed, S., Banerjea, A. C. Hyperactivation of mammalian target of rapamycin complex 1 by HIV‐1 is necessary for virion production and latent viral reactivation. FASEB J. 31, 180–191 (2017) www.fasebj.org